Sex as a main determinant of bi-atrial acute and chronic adaptation to exercise - Simard, F.; Sanz-de la Garza, M.; Vaquer-Seguí, A.; Blanco, I.; Burgos, F.; Alsina, X.; Prat-González, S.; Sitges, M. (European Journal of Applied Physiology, 2022)
Purpose Athlete`s heart encompasses multiple physiological cardiac adaptations, although less is known at atrial level. How sex may influence the type and extent of atrial adaptations to exercise stimuli is also unknown. Our objective was to compare gender differences of echocardiographic atrial function indices in response to exercise in endurance athletes (EAs).